The Interrupted Life. - Morin, France (New York : The New Museum of Contemporary Art, 1991)
Artaud, Antonin ; Beuys, Joseph ; Blake Nayland ; Boltanski, Christian ; Bouillon, victor ; Cadieux, Genevieve ; Calle, Sophie ; Carlson, Mary ; Charlesworth, Sarah ; Clark, Larry ; Dunuser, Hans ; DeSana, Jimmy ; Dittborn, Eugenio ; Drozdik, Orshi ; Dumas, Marlene ; Durham, Jimmie ; etc.
The Interrupted Life, The New Museum of Contemporary Art, New York, September 12 - December 29, 1991
boek